Increased Interleukin-1 (IL-1) and Imbalance between IL-1 and IL-1 Receptor Antagonist during Acute Inflammation in Experimental Shigellosis - Arondel, Josette (American Society for Microbiology, 1999)
Infection by the enteric bacterial pathogen Shigella results in intense mucosal inflammation and destruction of the colonic and rectal epithelium in infected humans. Initial bacterial translocation occurs through the follicle-associated epithelium. Previous experiments suggest that interleukin-1 (IL-1) is crucial to trigger inflammation, particularly in the follicular zones. During the first 4 hours of infection in a rabbit ligated-loop model of intestinal invasion, there are two salient characteristics: (i) a high concentration of IL-1α and IL-1β, both in infected Peyer's patch tissue and in the corresponding efferent mesenteric blood, and (ii) a very low level of expression of IL-1 receptor antagonist (IL-1ra). These may reflect a combination of regulation of expression and secretion of IL-1α, IL-1β, and IL-1ra by both resident and recruited phagocytes and the induction of mononuclear phagocyte apoptosis by Shigella. This low IL-1ra/IL-1 ratio likely accounts for the rapid, uncontrolled inflammation characteristic of shigellosis.